Uji Stabilitas Fisik Losio Yang Mengandung Fraksi Diklorometana Ekstrak Metanol Kulit Buah Manggis (Garcinia mangostana L.) - Apriyanti, Elis; Jufri, Mahdi; Elya, Berna (Majalah Ilmu Kefarmasian, 2012)
Mangosteen pericarp (Garcinia mangostana L.) contains some of xanthones derivates which have antioxidant activity.Those compounds prevent formation of free radicals that cause premature aging. Dichloromethane fraction from methanol extract of mangosteen pericarp has very strong antioxidant activity. Dicholomethane fraction of mangosteen pericarp was formulated into lotion dosage form with different concentration 0.01; 0.05; and 0.25%.. Physical stability of lotion was evaluated by cycling test, centrifugal test, and stored the lotions at low temperature (4±2˚C), room temperature (27±2˚C), dan high temperature (40±2˚C). The result showed that the lotions stable at each strorage condition and cycling test. However, the result of centrifugal test showed separation phase of lotions.